Pericapsular nerve group (PENG) block: A feasibility study of landmark based technique - Jadon, Ashok (Indian J Anaesth, 2020)
BACKGROUND: Pericapsular nerve group (PENG) block is a new ultrasound guided nerve block. It was used primarily to relieve pain in hip fracture; now, many new indications have been added. However, dependency on ultrasound guidance for this block limits its use where ultrasound facility is poor or not available. We have suggested a landmark based technique to increase the benefit of this novel nerve block. AIM AND OBJECTIVES: To do a feasibility study to assess the successful placement of block needle, clinical efficacy of the block and block-related complications. MATERIAL AND METHODS: Total 10 patients (4 males and 6 females) with fracture hip and scheduled for hip surgery under spinal anaesthesia were selected for the study. In 4 patients ultrasound guided PENG block using out-of-plane approach and in 6 patients landmark based nerve stimulator guided block was given with 20ml 0.25% bupivacaine and 8mg dexamethasone. Pain relief before and after 30 minutes of block was assessed by numeric rating scale (NRS) and comfort during spinal position was assessed by ease of spinal position score (EOSP). RESULTS: All 10 patients had successful block; NRS at rest was 6 (6-9) Vs 2 (0-2) and on 15 °limb elevation was 8 (8-10) Vs 3 (2-4). All patients could sit comfortably during spinal anaesthesia and median (range) EOSP sore was 3 (2-3). No complication was observed. CONCLUSION: Landmark based technique for PENG block is a feasible option and can be used safely where ultrasound facility is not available.